2D black phosphorus and tungsten trioxide heterojunction for enhancing photocatalytic performance in visible light. Issue 46 (23rd July 2020) - Wang, Qi; Li, Bihan; Zhang, Ping; Zhang, Wenming; Hu, Xiaoru; Li, Xiaochen
Abstract : BPNs in the WO3 –BPNs heterojunction acted as a co-catalyst to enhance photo-generated electron–hole pairs separation and improve degradation performance. Abstract : A novel, efficient and stable 2D black phosphorus and tungsten trioxide heterojunction (WO3 –BPNs) was successfully synthesized using a combined hydrothermal, liquid phase exfoliating and co-precipitation method. The as-obtained WO3 –BPNs composite was characterized by using XRD, SEM, XPS, UV-vis, etc. The results showed that the bandgap energy of the WO3 –BPNs50 sample was 2.2 eV, which was lower than that of pure WO3 . BPNs in the WO3 –BPNs heterojunction as a co-catalyst effectively enhanced photo-generated electron–hole pairs separation. The synthesized WO3 –BPNs sample significantly improved the photocatalytic performance in degrading rhodamine B (RhB) and metoprolol (MET) compared to pure WO3 and BPNs under visible-light. The maximum RhB and MET removal efficiencies were 92% and 87%, respectively, in the WO3 –BPNs50 (added 50 mL BPNs dispersion) sample within 120 minutes. The relevant photocatalysis mechanisms were discussed. In addition, the intermediate products in the MET photodegradation process were investigated by LC-MS technology, and the degradation pathway of MET was proposed.